2017
DOI: 10.1016/j.jcmgh.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Alpha Promotes Th1 Response and Epithelial Apoptosis via Inflammasome Activation in Human Intestinal Mucosa

Abstract: Backgound & AimsSeveral lines of investigation suggest that interferon (IFN) alpha can alter human intestinal mucosa homeostasis. These include the endogenous production of IFN alpha in celiac disease or inflammatory bowel diseases, as well as the occurrence of intestinal side effects of exogenous IFN alpha used as a therapeutic tool. Here, we present an ex vivo translational approach to investigate the effects of IFN alpha on the human normal intestinal mucosa, as well as its underlying mechanisms.MethodsHuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
(54 reference statements)
2
29
0
4
Order By: Relevance
“…Within reovirus-infected cells, NF-B and IRF-3 are required for maximum levels of apoptosis (25,(44)(45)(46). It is possible that cytokines induced by NF-B and IRF-3, including type I interferons, activate death pathways in adjacent, uninfected cells (47)(48)(49)(50). In addition, triggering enterocyte death would restrict viral replication and limit the amount of antigen observed by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…Within reovirus-infected cells, NF-B and IRF-3 are required for maximum levels of apoptosis (25,(44)(45)(46). It is possible that cytokines induced by NF-B and IRF-3, including type I interferons, activate death pathways in adjacent, uninfected cells (47)(48)(49)(50). In addition, triggering enterocyte death would restrict viral replication and limit the amount of antigen observed by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal epithelial lining is the first line of defense against potentially noxious agents including bacteria, bacterial products and viruses. Based on both primary cultures of normal human intestinal epithelial cells [ 1 ] and on ex vivo explant cultures of human normal colonic mucosa we have contributed to the emergence of the concept of innate immune functions as well as immunomodulatory functions of the human intestinal mucosa epithelium [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cellular and Molecular Gastroenterology and Hepatology , Jarry et al 1 showed that one of the type I interferons, interferon α (IFN-α), induces apoptosis and promotes intestinal epithelial barrier disruption by activating the inflammasome. The investigators used a 3-dimensional model of human normal colonic mucosa explant culture, an ex vivo system that not only maintains the architecture of the tissue but also contains various mucosal resident cells that can interact to trigger an innate immune response.…”
mentioning
confidence: 99%
“…The human normal colonic explant culture allowed Jarry et al 1 to investigate how IFN-α affects intestinal mucosa homeostasis through a cross-talk between epithelial and immune cells and describe the mechanisms involved. The possibility of a direct effect of IFN-α in the human colonic epithelium, however, cannot be discarded completely.…”
mentioning
confidence: 99%
See 1 more Smart Citation